Involvement of Civil Society Institutions in Achieving Sustainable Development Goals (International Journal of Scientific Trends, 2024)
The article reveals the existing need to increase the openness and objectivity of monitoring the implementation of programs for the socio-economic development of regions by involving state and economic management bodies, representatives of civil society institutions, business circles and the media in its implementation. It also analyzes the level of development of the relevant procedural rules that determine the mechanisms for the implementation of non-governmental non-profit organizations and other civil society institutions of the rights and powers granted to them by law, including their weak involvement in the processes of developing national development plans, the lack of active and effective participation of non-governmental organizations in monitoring the fulfilment of state commitments on achieving sustainable development goals.